2005
DOI: 10.1097/01.mib.0000178262.95980.65
|View full text |Cite
|
Sign up to set email alerts
|

Venular Constriction of Submucosal Arterioles Induced by Dextran Sodium Sulfate

Abstract: The results are consistent with a proposed mechanism in which thromboxane constricts submucosal arterioles when the arterioles are closely paired with platelet-bearing venules in DSS-induced inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 28 publications
2
25
0
Order By: Relevance
“…In spontaneously hypertensive rats, treatment with cyclooxygenase inhibition or thromboxane receptor antagonists abolished the constriction observed in arterial rings [1]. Additionally, intestinal inflammation induced by dextran sodium sulfate (a model of colitis) was found to induce thromboxane-dependent arteriolar constriction, but only in arterioles closely paired with venules having adherent leukocytes and platelets [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In spontaneously hypertensive rats, treatment with cyclooxygenase inhibition or thromboxane receptor antagonists abolished the constriction observed in arterial rings [1]. Additionally, intestinal inflammation induced by dextran sodium sulfate (a model of colitis) was found to induce thromboxane-dependent arteriolar constriction, but only in arterioles closely paired with venules having adherent leukocytes and platelets [12].…”
Section: Discussionmentioning
confidence: 99%
“…The antagonist partially reduced the vasoconstriction, suggesting that one or more other constricting mediators could be involved in their model of ischemia-reperfusion [22]. Thromboxane also appears to play a role in the venule-dependent arteriolar constriction observed in a model of intestinal inflammation induced by dextran sodium sulfate [14].…”
Section: Introductionmentioning
confidence: 99%
“…We and others (16,20,40) have earlier observed that the degree of inflammation in DSS-induced colitis tends to be greater in the distal than in the proximal colon. This is confirmed here in the histological sections as well as in the P-selectin expression, which was three times higher in the distal compared with the proximal and transverse colon.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that platelet adhesion within postcapillary venules was highly dependent on leukocyte adhesion, with ϳ45% of adherent leukocytes binding platelets in a model of ischemia-reperfusion (4). Activated platelets can release the potent vasoconstrictor thromboxane, which has been implicated in a recent study (8) in which platelet adherence in venules was associated with constriction of closely paired arterioles in a model of dextran sodium sulfate-induced inflammation. Figure 8 shows the mechanism that has been proposed to explain the role of venular adenosine and adherent leukocytes in regulation of the resting diameter of closely paired arterioles.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to normal physiological conditions, the presence of inflammatory cells in venules may have a major influence on arteriolar constriction (8,33). Zamboni et al (33) found that arterioles in reperfused (previously ischemic) skeletal muscle, but only arterioles near inflamed venules (as assessed by the presence of adherent leukocytes), were constricted.…”
mentioning
confidence: 99%